2020
DOI: 10.1101/2020.04.16.20065920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes of hydroxychloroquine usage in United States veterans hospitalized with Covid-19

Abstract: BACKGROUND:Despite limited and conflicting data on the use of hydroxychloroquine in patients with Covid-19, the U.S. Food and Drug Administration has authorized the emergency use of this drug when clinical trials are unavailable or infeasible. Hydroxychloroquine, alone or in combination with azithromycin, is being widely used in Covid-19 therapy based on anecdotal and limited observational evidence. METHODS:We performed a retrospective analysis of data from patients hospitalized with confirmed SARS-CoV-2 infec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
238
1
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(262 citation statements)
references
References 19 publications
6
238
1
14
Order By: Relevance
“…HCQ (Geleris et al, 2020;Mahevas et al, 2020;Magagnoli et al, 2020). However, based on the results in these studies, it is very likely that they used high doses of HCQ, which might induce cardiotoxicity and death.…”
Section: Discussionmentioning
confidence: 99%
“…HCQ (Geleris et al, 2020;Mahevas et al, 2020;Magagnoli et al, 2020). However, based on the results in these studies, it is very likely that they used high doses of HCQ, which might induce cardiotoxicity and death.…”
Section: Discussionmentioning
confidence: 99%
“…22 As presented in the previous section, 1 observational study 23 in 120 patients with mixed-severity COVID-19 provides very low-quality evidence that lopinavir-ritonavir may increase viral clearance at day 23 (Appendix 3). 22 Very low-quality evidence from 181 patients with severe COVID-19 and 255 patients with mixedseverity disease in 2 observational studies (preprints) 37,38 raised the possibility that hydroxychloroquine may increase mortality and the need for mechanical ventilation (Appendix 3). 22…”
Section: Direct Evidencementioning
confidence: 99%
“…We did not study the clinical usefulness of these interventions in term of clinical improvement such as attenuation of the disease severity or mortality reduction. However, we are aware of the negative study that showed no reduction in mechanical ventilation risk in patients hospitalized with Covid-19 and received HCQ, either with or without azithromycin (23).…”
Section: Discussionmentioning
confidence: 97%